Stakeholders’ Risk Perceptions of Decarbonised Energy System: Insights into Patterns of Behaviour - Farid Karimi (MDPI AG, 2021)
According to EU goals and the Paris Agreement, an urgent need exists for reducing CO2 emissions while still securing energy supply. Thus, the timely deployment of carbon capture and storage (CCS) is seemingly unavoidable, especially for the cement and steel industries. However, diverse perceptions of CCS among stakeholders such as experts, politicians, and laypeople exist that could hinder the deployment of the technology. Hence, it is worthwhile to recognise these diverse perceptions and their roots. In the studies on risk perceptions, the emphasis has been mostly on the public, as well as factors that influence the public, such as knowledge dissemination and trust. Although these are crucial elements, they are not enough to explain the complexity of risk perceptions. In contrast to the mainstream research, this paper hypothesises that both laypeople and experts are affected by common cultural denominators, therefore, might have similar patterns of risk perceptions. This research suggests a framework that explains the role of societal culture in risk governance, arguing that thrifty, uncertainty avoidant, hierarchical societies tend to have a higher risk perception of CCS. This study is based on a synthesis of the earlier research, an extensive literature review, and an analysis of interviews data.